Performance Effectiveness of Social Engineering in The Implementation of Climate Village Program in Wates, North Magelang - Oesman Raliby Al-Manan (Urecol Journal. Part G: Multidisciplinary Research, 2022)
Climate change and global warming have become the most talked-about environmental issues today. One of the government's efforts to follow up on climate change that is currently happening is by offering a program that refers to the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.84/Menlhk-Setjen/Kum.1/11/2016 concerning the Climate Village Program - PROKLIM. The purpose of this study was to evaluate the effectiveness of social engineering performance in encouraging the implementation of (PROKLIM) in the Wates Village area, Magelang City. This research includes action research, which is a research model that simultaneously practices and theorizes, or combines theory and at the same time implements it in practice to make a good contribution to the practical level of concern for the problems faced by society. The initiation of implementation (PROKLIM) in this area can be expected to have an impact on the local community. However, the minimization of social problems should be done through the application of social engineering with a community-based approach. Social engineering as an approach method in this research is carried out by providing information and increasing public understanding of everything related to climate change and the impacts that may occur. The results of this study prove that social engineering is able to move the community to be more independent, including waste management through decomposition reaching more than 63% of the amount of organic waste produced and 7.5 kg of dry maggot/group/batch. Working unit groups were also formed to support Proklim. So that the pattern of approaches taken with social engineering is considered quite effective.